Environmental impact of contaminated seawater remediated using new nanocomposites and the influence of climate change in bivalves - Coppola, Francesca (2022)
Recently, different approaches have been applied for water remediation purposes, including the use of nanoparticles (NPs) to remove metals and metalloids from water as advantageous alternatives to traditional water treatment methods. Among these new NPs, the synthesis of multifunctional nanocomposites based on graphene and on manganese-ferrite has received considerable attention due to their huge capacity to remove metal(loid)s from waters. However, research dedicated to new and specific environmental risks related to these nanomaterials is limited. Furthermore, impacts induced by the combination of climatic change factors (namely salinity shifts and increase of temperature) and contaminants such as metal(loid)s (e.g. mercury, arsenic and lead) in aquatic systems, are yet unidentified. To evaluate the impacts of all these factors, benthonic species can be a good model as they are affected by several environmental constraints. Particularly, bivalves as Mytilus galloprovincialis (mussels) and Ruditapes philippinarum (clams) have been identified by several authors as bioindicators that respond quickly to environmental disturbances, with a wide spatial distribution and economic relevance. Thus, the present thesis evaluated the ecotoxicological safety of remediated seawater previously contaminated with metal(loid)s and remediated by using graphene oxide functionalized with polyethyleneimine (GO-PEI) or/and manganese-ferrite NPs (MnFe2O4-NPs) on M. galloprovincialis and R. philippinarum species. For this, histopathological and biochemical alterations were carried out, towards a deeper understanding of the alterations induced in both species by these materials after the remediation. Results obtained showed that organisms exposed to noncontaminated (control condition) and remediated seawater treatments presented similar biological patterns, with no considerable differences expressed in terms of biochemical and histopathological alterations. Moreover, the present findings revealed increased toxicological effects in bivalves under climatic changes in comparison to those under control temperature and salinity. These results confirm the capability of GO-PEI and MnFe2O4-NPs to adsorb metal(loid)s from water with no noticeable toxic effects, although temperature rise and salinity shifts could affect the responses of bivalves to remediated seawater. Although, bivalves exposed to these NPs showed slight oxidative stress, cellular damage and neurotoxicity as well as histopathological alterations in comparison to the control, the materials seem to be a promising eco-friendly approach to decontaminated wastewater.